Growth of hBN Using Metallic Boron: Isotopically Enriched h10BN and h11BN. Issue 1635 (16th January 2014) - Hoffman, T.B.; Zhang, Y.; Edgar, J.H.; Gaskill, D.K.
ABSTRACT: Hexagonal boron nitride (hBN) crystals enriched in 10 B and 11 B isotopes were synthesized using a high temperature (1500° C) Ni-Cr-B reactive-precipitation growth under a N2 atmosphere. Two growth mechanisms were observed: conventional defect-facilitated bulk growth which produced crystals with a platelet-like habit with width and thickness of 20-30 μm and 5 μm, respectively, and vapor-liquid-solid interface growth of hBN whiskers with lengths and diameters as large as 70 μm and 5 μm, respectively. Similar growth mechanisms were seen for samples enriched in either isotope. Isotopic analysis via secondary-ion mass spectrometry showed boron concentrations of 84.4 at% and 93.0 at% for the majority isotopes in the 10 B-rich and 11 B-rich samples, respectively. Raman spectroscopy showed an increase in peak Raman shift for the 10 B-rich sample, having two barely resolved peaks at 1393.5 and 1388.8 cm -1, and a decrease for the 11 B-rich sample, having peak at 1359.5 cm -1 (FWHM of 9.4 cm -1 ), compared to that of natural hBN, with its peak at 1365.8 cm -1 (FWHM of 10.3 cm -1 ). Raman shift showed a linear trend with increasing 10 B concentration allowing for a calibration curve to be developed to estimate 10 B enrichment in hBN using non-destructive methods.